Discrete element method simulation of a conical screen mill: A continuous dry coating device. (24th March 2015) - Deng, Xiaoliang; Scicolone, James; Han, Xi; Davé, Rajesh N.
Abstract: A conical screen mill or a comil is a frequently used device for powder delumping. It has been recently shown as a promising continuously operating device for powder dry coating. In order to examine the influence of the operating parameters of comil, which has rather complex geometry, discrete element method (DEM) modeling was carried out and the residence time distribution (RTD) and mean residence time (MRT) were computed. The simulation results show that MRT increases with increasing impeller speeds, an outcome that is counter-intuitive. Limited experimental investigation showed a qualitative agreement with corresponding simulation results. Simulation results also showed that MRT increases with decreasing feed rates, decreasing open areas, and decreasing screen hole sizes. In addition to computing the RTD and MRT, the relationship between average collision number (ACN), number of particles inside the transition zone (region above the conical part), and MRT was examined indicating that higher impeller speed leads to longer MRT and larger ACNs. In contrast, the equilibrium number of particles inside the comil decreases with increasing feed rate, open area, and screen hole size, therefore, leading to a decrease in both MRT and ACNs. Such analysis shows that increasing impeller speed forces more particles to stay in the transition zone, leading to increased MRT; hence increased MRT may not always lead to improved dry coating. Overall, the results demonstrate the relationship between MRT and various operating parameters, while shedding light on the impact of ACNs on MRT, hence providing better understanding of the complex dynamic process and the selection of experimental conditions. Graphical abstract: Discrete element method (DEM) is used to investigate the comil (conical screen mill), which is a continuous powder processing device, recently gaining popularity for dry particle coating. Simulations show that the mean residence time (MRT) is one of the most critical parameters, and along with the process and collision dynamics can explain comil dry coating results, and may allow selection of experimental operating conditions. Highlights: Discrete element method (DEM) is used to investigate the comil (cone mill) process. Mean residence time (MRT) increases with impeller speed, validated by experiment. Dominating collision type changes depending on operating parameters. The relation between MRT, collision number, and operating parameters is identified. The MRT along with collision/process dynamics can explain comil dry coating results.